Efektivitas Dakwah Fiâah: Studi Model Dakwah pada Lembaga Dakwah Kampus - Setiawan, Asep Iwan (Jurnal Ilmu Dakwah, 2011)
Campus Daâwah Institution (CDI) is a movement who which done by student especially in giving members comprehension about their religious behavior. One of destination, to increase comprehension about their religion throught mentoring that done each Monday, so the members become trained and consistence in achieving their destination, with itâs indicator such as: ritual involving, ideology, intellectual, experience and consequencial.